Development and the search for connection. Issue 10 (3rd October 2019) - Fechter, Anne-Meike
Abstract: The stated purpose of development is often characterised by the motivation to 'help' – that is, to intervene in the lives of others in supportive ways. This paper argues that this perspective has obscured how development activities are also animated by its twin desire to 'connect'. While this holds significance for development more broadly, it becomes particularly evident in a mode of assistance that has gained prominence more recently. These are privately funded, small-scale projects led by individual founders, here described as 'citizen aid'. Based on ethnographic research among citizen aid initiatives in Cambodia, the paper argues that the relevance of 'connecting' has been insufficiently recognised so far. It explores different aspects of what participants mean by 'making a connection', including face-to-face contact, direct experience of aid activities, and their tangible efficacy. It also finds that establishing interpersonal relationships across national, ethnic and cultural differences, while potentially challenging, is a key motivation for those involved. Finally, the paper argues that acknowledging the desire to connect questions notions of the 'distant stranger' as the archetypical humanitarian object, highlighting the wish for familiarity and closeness as potentially just as important for motivating and directing assistance to others.